THE INFLUENCE OF PERCEIVED ORGANIZATIONAL SUPPORT, WORKLOAD, AND JOB SATISFACTION ON WORK ENGAGEMENT AMONG MARINE SERVICE SHIPPING INDUSTRY EMPLOYEES AT CV. BERKAT ABADI BITUNG - San Remo Sineri; Kadek Rai Suwena; Komang Krisna Heryanda (SOSIOEDUKASI, 2026)
This study aims to analyze the influence of perceived organizational support, workload, and job satisfaction on work engagement among employees in the marine service shipping industry at CV. Berkat Abadi Bitung. The research applies a causal quantitative approach with perceived organizational support, workload, and job satisfaction as independent variables and work engagement as the dependent variable. The population consisted of all 41 employees of the company, and a saturated sampling technique was used so that the entire population became the research sample. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using multiple linear regression. The results indicate that perceived organizational support, workload, and job satisfaction each have a significant partial effect on work engagement. Among these variables, job satisfaction shows the strongest influence on employee engagement. Furthermore, the simultaneous test confirms that the three variables collectively have a significant effect on work engagement. The coefficient of determination shows that 92.6% of the variation in work engagement can be explained by perceived organizational support, workload, and job satisfaction. These findings highlight the importance of strengthening organizational support, managing workloads proportionally, and improving job satisfaction to enhance employee engagement and organizational performance